Sosialisasi Nilai Tambah dari Bahan Eco – Enzyme dan Manfaat Menjaga Lingkungan Hijau Berkelanjutan Melalui Hibrid Eksperimental pada Siswa SMP Stela Matutina, Kota Salatiga - Adinda Maharani; Bima Setya; Vinsent Brilian Adiguna; Krist Krist; Maradona Asri (Jurnal Pengabdian Masyarakat Waradin, 2024)
Making eco-enzymes is a method of processing organic waste without residue or a zero waste approach. Currently, socialization or education regarding waste processing using the eco-enzyme method in schools, especially at the city/district level, is still very limited, as a result there is still minimal understanding of what organic waste processing can be done, and it is generally only known as making compost. This service involves university teams, school teachers and junior high school students. The aim of this service is to teach Stella Matutina Junior High School students in Salatiga City about how to convert organic waste into high-value eco-enzyme products. The choice of making liquid soap was because the materials used were environmentally friendly and the process tended to be easy, making it suitable for junior high school students. The method used is implementing experimental hybrid learning, starting from socialization, mentoring, to sustainability of this program. The result of this service is that students' knowledge of environmental programs increases and students are actively involved in achieving environmental KPI.